2016
DOI: 10.1136/gutjnl-2015-310255
|View full text |Cite
|
Sign up to set email alerts
|

BVES regulates c-Myc stability via PP2A and suppresses colitis-induced tumourigenesis

Abstract: Objective Blood vessel epicardial substance (BVES) is a tight junction-associated protein that regulates epithelial-mesenchymal states and is underexpressed in epithelial malignancy. However, the functional impact of BVES loss on tumorigenesis is unknown. Here we define the in vivo role of BVES in colitis-associated cancer (CAC), its cellular function, and its relevance to inflammatory bowel disease (IBD) patients. Design We determined BVES promoter methylation status using an Infinium HumanMethylation450 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 45 publications
2
64
0
Order By: Relevance
“…To date, evidence on the effects of POPDC1 on cell proliferation and its interaction with molecules in pathways that regulate cell proliferation such as Zonula occludens-1 (ZO-1), Wnt and c-Myc, are consistent with POPDC1 being a regulator of cell proliferation and its loss or suppression of function enhancing malignant cell behavior [7,10,41,42]. The loss of POPDC1 function has further been shown to enhance cell migration, proliferation, and invasion in many solid tumors [10,37,38,[42][43][44]. Furthermore, POPDC1 expression is significantly suppressed at all clinical stages of breast [43] and gastric cancer [45] without correlation to clinical progression.…”
Section: The Roles Of Popdc Proteins In Cell Proliferationmentioning
confidence: 97%
See 2 more Smart Citations
“…To date, evidence on the effects of POPDC1 on cell proliferation and its interaction with molecules in pathways that regulate cell proliferation such as Zonula occludens-1 (ZO-1), Wnt and c-Myc, are consistent with POPDC1 being a regulator of cell proliferation and its loss or suppression of function enhancing malignant cell behavior [7,10,41,42]. The loss of POPDC1 function has further been shown to enhance cell migration, proliferation, and invasion in many solid tumors [10,37,38,[42][43][44]. Furthermore, POPDC1 expression is significantly suppressed at all clinical stages of breast [43] and gastric cancer [45] without correlation to clinical progression.…”
Section: The Roles Of Popdc Proteins In Cell Proliferationmentioning
confidence: 97%
“…The protein is tethered to the plasma membrane as a dimer that in the case of POPDC1 is stabilized by a disulfide bridge. The Popeye domain serves as a specific high-affinity binding site for cAMP [10].…”
Section: The Popdc Protein Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Parang et al conducted the first in vivo study testing BVES as a tumor modifier. 54 Using the wellestablished azoxymethane repeated cycles of dextran sodium sulfate (AOM/DSS) 55-58 model of inflammatory carcinogenesis, they showed that Bves-/-mice developed worse inflammatory injury, greater tumor multiplicity, and a higher degree of intratumoral dysplasia. The authors observed increased intratumoral Wnt signaling at the protein level.…”
Section: Bves As a Tumor Suppressormentioning
confidence: 99%
“…Interestingly, they showed that the BVES promoter was also hypermethylated in distant, non-malignant mucosa of patients who also had colitis-associated cancer, suggesting that BVES promoter methylation status could be used a biomarker of distant cancer. 54 The current method of cancer screening in inflammatory bowel disease patients, who are at a significantly elevated risk of developing colitisassociated cancer, 69 is surveillance colonoscopy, in which the colon is biopsied with the hope that cancer can detected at an early and therefore treatable stage. However, the screening for malignancy in the colon of inflammatory bowel disease patients can be challenging because the lesions are frequently flat, making it difficult to identify, especially in the setting of inflammatory changes.…”
Section: Bves Promoter Methylation As a Biomarker In Malignancymentioning
confidence: 99%